Indexing and retrieval of multimodal lecture recordings from open repositories for personalized access in modern learning settings - Guetl, Christian; Chang, Vanessa; Franco, A.; Sampaio, P.; Kappe, F. (AACE, 2009)
An increasing number of lecture recordings are available to complement face-to face and the more conventional content-based e-learning approaches. These recordings provide additional channels for remote students and time-independent access to the lectures. Many universities offer even complete series of recordings of hundreds of courses which are available for public access and this service provides added value for users outside the university. The lecture recordings show the use of a great variety of media or modalities (such as video, audiom lecture media, presentation behaviour) and formats. Insofar, none of the existing systems and services have sufficient retrieval functionality or support appropriate interfaces to enable searching for lecture recordings over several repositories. This situation has motivated us to initiate research on a lecture recording indexing and retrieval system for knowledge transfer and learning activities in various settings. This system is built on our former experiences and prototypes developed within the MISTRAL research project. In this paper we outline requirements for an enhanced lecture recording retrieval system, introduce our solution and prototype, and discuss the initial results and findings.